Direct Numerical Simulation of Vertical Rotating Turbulent Open-Channel Flow with Heat Transfer (Communications in Computational Physics, 2018)
Direct numerical simulation of vertical rotating open-channel flow with heattransfer has been carried out for the rotation number Nτ from 0 to 0.1, the Prandtlnumber 1, and the Reynolds number 180 based on the friction velocity of non-rotatingflow and the height of the channel. The ob jective of this study is to reveal the effect of rotation on the characteristics of turbulent flow and heat transfer, in particularnear the free surface and the wall of the open-channel. Statistical quantities, e.g., themean velocity, temperature and their fluctuations, turbulent heat fluxes, and turbulence structures, are analyzed. The depth of surface-influenced layer decreases with theincrease of the rotation rate. In the free surface-influenced layer, the turbulence andthermal statistics are suppressed due to the effect of rotation. In the wall-influencedregion, two typical rotation regimes are identified. In the weak rotation regime with0 < Nτ < 0.06 approximately, the turbulence and thermal statistics correlated with thespanwise velocity fluctuation are enhanced since the shear rate of spanwise mean flowinduced by Coriolis force increases; however, the other statistics are suppressed. Inthe strong rotation regime with Nτ > 0.06, the turbulence and thermal statistics aresuppressed significantly because the Coriolis force effect plays a dominant role inthe rotating flow. To elucidate the effect of rotation on turbulent flow and heattransfer, the budget terms in the transport equations of Reynolds stresses and turbulent heat fluxes are investigated. Remarkable change of the direction of streakstructures based on the velocity and temperature fluctuations is discussed.